Principal and Teacher Perceptions of the Duration of Classroom Observations and Evaluative Feedback - Pyle, David (Southwest Baptist University, 2018)
This quantitative study was conducted to describe and compare the perceptions of Missouri secondary principals and teachers regarding the duration of classroom observations and evaluative feedback. The study explored the effects of variation in classroom observation durations from the perspective of both principals and teachers. A survey instrument was used to sample participants to address the research questions guiding the study. Responses from principals indicated greater agreement in perceptions regarding the adequacy of reported observation durations than effects of observation duration. Principals also indicated greater agreement in perceptions regarding the characteristics of evaluation feedback than the impact of the feedback. The perceptions of principals did not differ significantly according to the reported duration of observations. Responses from teachers indicated greater agreement in perceptions regarding the effects of observation duration than the adequacy of reported observation durations. Teachers also indicated greater agreement in perceptions regarding the characteristics of evaluation feedback than the impact of the feedback. The perceptions of teachers reporting shorter observation differed significantly from those reporting longer observation durations. Statistically significant differences were found between the perceptions of principals and teachers. Principals indicated significantly greater agreement in perceptions regarding observation duration and evaluation feedback. The durations and frequencies of observation reported by principals and teachers indicate the trend toward shorter and more frequent observations was present in Missouri secondary schools.